EMPIRICAL ANALYSIS OF DEBT RECOVERY STRATEGY EFFECTIVENESS AND NON-PERFORMING LOAN MITIGATION IN GHANAIAN MICROFINANCE INSTITUTIONS: EVIDENCE FROM THE ASHANTI REGION - Daniel Amoah; Doris Boakye (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
High non-performing loans (NPLs) threaten the sustainability of microfinance institutions (MFIs) in emerging markets like Ghana. This study investigates the effectiveness of debt recovery strategies, their impact on NPLs, and implementation challenges faced by MFIs in the Ashanti Region. Using a mixed-methods approach, data were collected from 315 respondents across 11 strategically selected MFIs through stratified sampling. Multivariate regression analysis assessed the impact of strategies on NPLs, while qualitative analysis explored implementation barriers. Grounded in agency theory, social capital theory, and relationship banking theory, the study finds that debt recovery strategies collectively explain 65.1% of NPL variation. Regular monitoring (β=0.235, p=0.003) and delinquency follow-up (β=0.232, p=0.001) have the most significant effects. Although borrower education is widely implemented, it shows limited statistical impact (β=0.022, p=0.748), highlighting a disconnect between perceived and actual effectiveness. Key implementation challenges include economic downturns, limited credit information infrastructure, and weak borrower cooperation. The study contributes a relationship-based framework for sustainable loan performance, advocating long-term partnerships over enforcement-focused approaches. It advances microfinance research by analyzing multiple strategies simultaneously rather than in isolation. Policy recommendations include creating shared credit databases, introducing counter-cyclical support measures, and promoting regulatory frameworks aligned with relationship banking. Practically, the findings help MFIs prioritize monitoring and follow-up in resource allocation, offering actionable insights for sustainable microfinance in Ghana and comparable emerging markets.